Pelatihan Pendampingan Konsep Pembelajaran Green Economy Guru Untuk Membentuk Karakter Siswa Sekolah Dasar - Setiawan, Bramianto; Mukhlis, Septian; Ruwaida, Gina Asri; Salsabila, Deby Anatasya; Cahyo, Ikhsan Fauzi; MS, Zulela (Pusmedia Group Indonesia, 2025)
The issue of environmental sustainability is increasingly receiving global attention, including in basic education. Schools as educational institutions have an important role in instilling environmental awareness in the younger generation, one of which is through the integration of the green economy concept in learning. The green economy focuses on sustainable economic growth by paying attention to environmental, social, and economic aspects. However, research shows that elementary school teachers' understanding of this concept is still limited, which has an impact on the lack of optimal internalization of sustainability values in learning. Therefore, training and mentoring for teachers is essential to improve their understanding and skills in integrating the green economy in learning. This service program aims to provide participatory-based training to elementary school teachers in South Tangerang City, with a focus on developing character-based and sustainability teaching tools. This community service activity is carried out through a participatory training and mentoring approach. The design refers to a community-based education model that emphasizes active cooperation between the implementation team and the participants, namely elementary school teachers. The results of the activity showed a significant increase in teachers' understanding and skills in integrating the concept of green economy in learning, through project-based learning techniques that are relevant to the environmental context. The program has also succeeded in fostering awareness of the importance of continuing education and contributing to the character development of students who care about global environmental issues.